(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The transition to a post-industrial, information society requires from a person living and acting in a constantly changing world the ability to independently search and make decisions, to act responsibly, to self-realize in various life situations, and to possess the necessary competencies in the professional field of activity to strengthen one’s competitiveness.